INCIDENCE OF BEGOMOVIRUS INFECTING TOMATO (SOLANUM IYCOPERSICUM) AND PEPPER (CAPSICUM SPP.) CROPS IN SELECTED AREAS IN CEBU, PHILIPPINES - Pascual, Maria Lima D (Journal of Agriculture and Technology Management; Vol 25 No 1 (2022): Vol 25 No 1 (2022): Journal of Agriculture and Technology Management (JATM) Volume 25 January - June 2022 Issue, 2024)
Begomoviruses (genus Begomovirus, family Geminiviridae ) are groups of plant viruses causing destructive diseases of vegetable crops worldwide. Several tomato- and pepper-infecting begomoviruses pose a major concern in crop production. In this study, the incidence of begomoviruses associated with tomato and pepper samples from Cebu, Philippines was determined through visual assessment of symptoms and detection of the virus by polymerase chain reaction (PCR) using two degenerate primers (TY1F/TY2R and PAL1v1978/PAR1c715H). Symptoms of begomovirus infection were observed in all the tomato and pepper farms visited. Infected tomato varieties exhibited severe to mild leaf curling and crinkling along with interveinal yellowing and plant stunting at early to late vegetative stage. In pepper crops, symptoms included severe leaf deformations (upward curling/cupping, crinkling and puckering) in addition to leaf discolorations (interveinal yellowing/mosaic). Results of PCR assays confirmed the presence of begomoviruses on both symptomatic tomato and pepper samples. In tomato, the expected DNA fragments of ~585 bp were successfully amplified in all samples while DNA-A component (~1.5 Kb fragment size) of the virus was generated in 88% of the total samples. In pepper, begomoviral coat protein (~565 bp) was detected in 42.5% of the samples with the gDNA as template. Using RCA-amplified DNA as a template, 75% (3/4) and 50% (2/4) of the RCA-amplified samples were positive of begomovirus. This study confirmed the prevalence of begomovirus on tomato and pepper crops in Cebu. Thus, early and rapid detection of these plant viruses provides a proactive strategy in dealing the disease and to mitigate yield losses.